2009
DOI: 10.1002/app.30146
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of in situ sodium‐activated and organomodified bentonite clay/styrene–butadiene rubber nanocomposites by a latex blending technique

Abstract: In this article, we describe a method used to prepare an in situ sodium-activated, organomodified bentonite clay/styrene-butadiene rubber nanocomposite master batch via a latex blending technique. The clay master batch was used for compound formulation. Octadecyl amine was used as an organic intercalate. The clay was purchased from local suppliers and was very cheap. Sodium chloride was used for in situ activation of the clay. The wide-angle X-ray diffraction data indicated that the in situ sodium activation h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…21 About 10 g of the unfractionated pristine bentonite clay was dispersed in 500 mL of distilled water using a Remi (India) stirrer for 1 h at 2000-3000 rpm. The temperature was maintained to around 80 C. Next sodium chloride (10% with respect to clay) was added to the hot clay slurry.…”
Section: Synthesis Of the In Situ Modified Bentonite Clay Nanocomposimentioning
confidence: 99%
See 1 more Smart Citation
“…21 About 10 g of the unfractionated pristine bentonite clay was dispersed in 500 mL of distilled water using a Remi (India) stirrer for 1 h at 2000-3000 rpm. The temperature was maintained to around 80 C. Next sodium chloride (10% with respect to clay) was added to the hot clay slurry.…”
Section: Synthesis Of the In Situ Modified Bentonite Clay Nanocomposimentioning
confidence: 99%
“…20 It is reported that at equivalent carbon black loading, the set property of the nanocomposites are inferior. 18 Author's previous publication 21 deals with a novel single step method to form in situ sodium activation and organo modified bentonite clay -SBR rubber nanocomposites. In this study, effect of silane treatment on the physical property of in situ sodium activation and organo modified bentonite clay -SBR rubber nanocomposites has been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, melt mixing was not able to realize this goal. Many research groups had reported their methods for preparing intercalation/exfoliation structure . In our previous study, new solutions and ultrasonication were introduced in the latex compounding process to improve the mix efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Rubber nanocomposites containing layered silicates (LS) as reinforcement have drawn the attention of researchers due to advantages that nanocomposites have over conventional composites. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The interest behind this development is placed on the nanoscale dispersion (the thickness of LS is ca. 1nm) and the very high-aspect ratio of the silicate platelets (length-to-thickness ratio up to 2000), which enable a high-reinforcing efficiency even at low-LS loading.…”
Section: Introductionmentioning
confidence: 99%
“…7,10,12,[14][15][16][17][18][19] The possibility to obtain elastomeric nanostructured systems by introducing modified LS in different types of elastomers has been investigated as well. [3][4][5][6]8,11 U.S. patent (065266,2005) 11 reports the preparation of nanocomposites comprised of water sellable clay particles in aqueous emulsions such as styrene butadiene rubber (SBR) or NR containing a novel amine to aid in the intercalation and partial exfoliation of the clay particles. The applications of such rubber nanocomposites are contemplated, for example, as aircraft tire tread, where a significant replacement of CB reinforcement is desired to reduce heat buildup for tire durability and to reduce tire weight for fuel economy.…”
Section: Introductionmentioning
confidence: 99%